The cider house rules [videorecording] - Hallstrom, Lasse, direction; Gladstein, Richard N. ([S.l] : Speedy Video, 2001)
The cider house rules tells a compelling and heartwarming story about how far a young man must travel to find the place where he truly belongs! Homer Wells has lived nearly his entire life within the walls of St. Cloud's Orphanage in rural Maine. Through groomed by its prorietor, Dr. Larch to be his successor, Homer nonetheless feels the need to strike out on his own and experience the world outside. Then, while working at an apple orchard, Homer falls for the beautiful Candy and learns some powerfully indelible lessons about life, love and home!
Screenplay, John Irving ; music, Rachel portman ; director of photography, Oliver Stapleton
Cast: Hopkins, Smith & Barden
Keywords: Young men -- Drama; Physicians -- Drama; Orphanages -- Drama